La técnica LINGUISTIC MIMICRY y su influencia en la producción oral del idioma inglés, componente: ritmo, entonación y stress en los estudiantes del curso de fonética del VI ciclo de la Escuela Académico Profesional de Idiomas de la UNSM-2013 - Solorzano De La Cruz, Kity Keren (2015)
This research work was carried out in the UNSM-T Professional Academic Language School in 2013 in which the VI cycle phonetics course students participated. Thus, the purpose of this investigation was to determine the influence of LINGUISTIC MIMICRY for improving oral production of English, component; rhythm, intonation and stress in the VI cycle phonetics course students of the UNSM-T Professional Academic Language School 2013, being that a deficiency was observed in the students not being able to express themselves orally in a natural way and as a native speaker, for which the technique LINGUISTIC MIMICRY was used and the main teaching methodology. For this, it was necessary to first design the technique, then carries it out and finally, establishes the influence that the technique had. The research is based in a constructivist approach, the same that manifests the existence and prevalence of active processes in new knowledge construction. Methodologically, this research work is approached from the experimental study perspective; being as only one experimental group was tested, and a pre-experimental level with a design that incorporates the application of a pre and post test to this group. In which the population consisted of the UNSM-T Professional Academic Language School students taking the VI cycle phonetics course students as the sample, made up of 17 females and 8 males; making a total of 25 students. The observation technique was used in which a validated evaluation sheet containing a series of items that assessed the student's progress in the development of the learning activities; and the students were also given the opportunity to assess the activity itself by means of a survey. The data processing made it possible to determine that the students scored low in terms of oral production in the component: rhythm, intonation and stress before applying the technique LINGUISTIC MIMICRY, and scored higher at the end of the application. Upon completion of this research, it was concluded that the technique LINGUISTIC mimicry has influenced significantly in terms of improving the oral production of the English language component: rhythm, intonation and stress in the VI cycle phonetics course students; this is shown in the pre and post test tables and in the consolidated grades of the 8 Learning Activities. This was such, thanks to the coordinately designed methodology for teaching and learning a second language.